Development of a Solar Power Plant in the Production Unit of SMK Muhammadiyah 2 Turi as a Green School Embodiment - Rinasa Agistya Anugrah; Erika Loniza; Venditias Yudha; Andika Wisnujati (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Implementing new and renewable energy (EBT) in Vocational High Schools can support the green school program. EBT is clean energy and clean technology that can be applied in the context of realizing a green school. Vocational High Schools whose curriculum is more inclined towards a practice that provides a more significant portion of skills to students, so skills are needed in technology, especially those related to EBT. Solar Power Plant (PLTS) is one of the EBTs that is easy to apply in green school-based vocational schools. Vocational High School 2 Turi is a Vocational High School that has implemented a green school-based school that needs to be given knowledge and skills about EBT and PLTS. Implementing this service consists of EBT counseling and PV mini-grid training. The EBT extension program and PLTS installation training participants were 20 students and ten teachers. EBT counseling increased students' knowledge by 70%, from 15% to 80% after counseling. Meanwhile, for teacher participants, there was an increase of 75% from 25% to 100%. The results of the PLTS installation training increased by 75% for all participants, student participants from 0% to 75%, and teachers from 5% to 80%. At the same time, the rest can improve their skills by practicing themselves in assembling PLTS components that have been granted.